Eletrogoniometria flexível : avaliação da simetria articular e dos efeitos dos sensores, das coletas e dos joelhos nos registros da marcha - Carnaz, Letícia (Universidade Federal de São Carlos, 2008)
Human movement recording is a fundamental tool for studies that perform movement analysis which is very useful for Physiotherapy and Biomechanics. However, to obtain high quality movement analysis, reliable and accurate equipments are necessary. In this way, flexible electrogoniometers have shown high reproducibility besides other advantages as low financial cost, readiness of working and bilateral data recording. Nevertheless, these equipments are exposed to errors like: the equipment itself, data acquisition procedures and the crosstalk effect. Thus, two studies (Studies I and II) were carried through. The aim of study (I) was to assess knee movement symmetry on sagittal and frontal planes based on Maupas criterion, absolute symmetry index and on statistical analysis. Nine healthy subjects have taken part in the study. Knee movements were recorded by flexible electrogoniometers attached on both knees. The subjects passed by a familiarization period in the treadmill and, after this, the movements were recorded during 90 seconds at 5,0 Km/h. The recording was partitioned as strides and normalized in time using a routine developed in MatLab. Movement curves were derived from 50 strides. Maximum angle and range of movement were also calculated. Based on Maupas criterion, subjects knees were considered symmetrical for the flexion-extension and valgus-varus movements. However the frontal plane movements showed more variability than sagittal plane movements, what can be due to some crosstalk effect. The aim of study (II) was to evaluate the effect from eletrogoniometer sensors, procedures (consecutive trials) and the knees during gait recordings. Knee flexion-extension and valgus-varus movements were recorded during treadmill walking. The recording was partitioned as strides and normalized in time using a routine developed in MatLab. Curves were derived from 50 strides, and seven conditions were evaluated: one for comparing two sensors; two for comparing two different trials (including variation due to sensor); and four for comparing right and left knee (including variation due to sensors and trials). Mean standard deviations of the differences were calculated. To estimate the variations due to trial and knee, the compound SDs were transformed into variances and split into its components. Differences between normal knees had more influence in determining variation on the results than sensors and trials for most of the subjects. Variation was much higher between knees for valgus-varus than for flexion-extension movements. Individual sensors showed the smaller source of variation. Thus, it is preferable to use different sensors in the same data recording (simultaneous) than use the same sensor in two different recordings (consecutive).
Keywords: Articulações; Articulação do joelho; Variação biológica; Eletrogoniometro; Erro; Confiabilidade; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL